Role of antioxidants in skin aging and the molecular mechanism of ROS: A comprehensive review - Narmin Hama amin Hussen; Sakar Karem Abdulla; Naza Mohammed Ali; Van Abdulqader Ahmed; Aso Hameed Hasan; Eman Erfan Qadir (Aspects of Molecular Medicine)
Skin aging is a multifaceted and gradual process influenced by both internal and external factors, including environmental stressors. These two mechanisms contribute to oxidative stress, triggered by ROS, which accelerates the aging of the skin. UV exposure increases the production of ROS in cells, which collectively contribute to the various skin changes linked to aging. However, the skin has a sophisticated antioxidant defense system that shields it from oxidative damage caused by both internal and external factors. The use of topical antioxidants have been shown to shield the skin from harmful free radicals generated intrinsically by regular cellular metabolism or as a result of UV light exposure. This review focuses on the assessment of the injury environmental factors cause to the skin, molecular mechanism of ROS in the skin aging, and the use of antioxidants to prevent that damaging and producing a protection against UV radiation from environmental factors. The systematic search was done for eligible articles which including in vivo and in vitro studies from studies between (1997 until 2024).